HUBUNGAN AKTIVITAS FISIK DENGAN KADAR GULA DARAH PADA PASIEN DIABETES MELLITUS TIPE 2 DI PUSKESMAS BINJAI ESTATE - Faswita, Wirda (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Diabetes mellitus (DM) is a dangerous disease because it can cause many complications. Physical activity is necessary for successful diabetes treatment. The aim of this study was to determine the relationship between physical activity and blood glucose levels in type 2 diabetes patients at the Binjai Estate Health Center. The type of research used is correlational research with a cross sectional design. The population of this study consisted of type 2 DM patients in the working area of ??the Binjai Estate Health Center from January 2020 to March 2020, using a purposive sampling technique, the population was 209. The sample size was taken 20% of the total population, namely 42 people (Arikunto, 2013). The data collection method used the Baecke questionnaire, analysis used the chi-square test with ? = 0.05. The research results showed that the majority of DM sufferers had the type with light physical activity, namely 21 people (50.00%) and the majority of DM sufferers had the type with KGD >200 mg/dL, namely 34 people (81.00%). The test results obtained Asymp.Sig value. (2 sides) = 0.000, namely <0.05, meaning there is a relationship between physical activity and blood sugar levels in type 2 DM sufferers at the Binjai Estate Health Center. It is recommended for diabetes mellitus sufferers to always be active in physical activity.